2019
DOI: 10.4102/jsava.v90i0.1765
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the knowledge and perceptions of veterinary students of antimicrobial resistance for future prescription of antimicrobials in animal health, South Africa

Abstract: Understanding the knowledge and perceptions of veterinary students of antimicrobial resistance (AMR) as potential future prescribers of antimicrobials may serve as an opportunity to improve stewardship of AMR. Pre-final (n = 42) and final (n = 29) year veterinary students of the University of Pretoria completed questionnaires to determine their knowledge and perceptions of AMR. Of the 71 respondents, mixed practice (48%) and small animal practice (45%) were the most preferred career choices post-graduation, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 28 publications
7
23
1
Order By: Relevance
“…Hence, resource allocations available to combat AMR in Nigeria have wide discrepancies with consequences of threatened food security in addition to an increased AMR challenge. There is a need to understand the current knowledge and propose means to bridge the existing gap on the trend, status, and situation of AMR arising primarily from food animals and the environment [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, resource allocations available to combat AMR in Nigeria have wide discrepancies with consequences of threatened food security in addition to an increased AMR challenge. There is a need to understand the current knowledge and propose means to bridge the existing gap on the trend, status, and situation of AMR arising primarily from food animals and the environment [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, veterinarians are very important stakeholders and play a vital role in the mitigation of AMR [8,[19][20][21]. The education, awareness, and training of veterinary students is vital to the improvement of antimicrobial use patterns in farms, clinics, and hospitals as well as in many animal species [8]. Veterinary students are future prescribers and their knowledge could influence progress in combating AMR [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of antibiotic resistance in Campylobacter jejuni is likely to be influenced by using antibiotic in both healthy and sick animals in poultry farms [ 27 ]. According to a study conducted by Smith et al, the veterinary students in South Africa perceived tetracycline, penicillin and sulphonamides to be the most abused antimicrobials [ 28 ]. Bester and Essack reported that tetracycline usage in South African animals’ production system is common [ 29 ].…”
Section: Antibiotic-resistant Pathogens In Africamentioning
confidence: 99%